Effect of R&D investment on firm value: evidence from the UK companies - Tong, Rui (2019)
This paper aims to evaluate the influence of R&D investment on firm performance and lagged period of firm performance by building models and analyzing data. To evaluate such a relationship we use a comprehensive dataset of firm-level observations from UK companies. It is divided into 3 main parts. The first part reviews the theoretical framework of this study testing R&D, firm performance and lagged effect basing on the theories of production function and economic growth, indicating that research and development activities can create knowledge. Then this study shows some of the literature that has been written to date about the relation between R&D investment and firm performance. The second part is the construction of data and models. The sample used consists of 245 companies from the UK. These companies are spread across five different industries with every industry represented by 49 companies. The industries being studied are Consumer goods, Consumer Services, Oil and Gas, Technologies and Industrial. for empirical analysis, this study uses the OLS regression model, Hausman test and fixed effect regression model based on our data structure. The third part consists of regression analysis and the implications of results. By using different control variables, including enterprise-scale, leverage ratio, and fixed asset ratio, the results indicate that the R&D investment in that year has a negative influence on business performance and a positive influence on enterprise value. However, this negative relation between R&D intensity and operating performance became positive in the very next year. Also, the lagged period of firm performance is two years and after that year (t-2) R&D investment became mature and have not effect on firm performance.